Teaching Methods of the Prophet (Peace Be Upon Him) Through Illustrative Drawings: The Hadith on "Hope and its Prolongation" as a Model (The International Journal of Educational Sciences and Arts, 2025)
The research aimed to explore the Prophetic teaching methods and their role in enhancing the educational process and improving learners' understanding. It began by outlining some of the Prophetic teaching methods, including but not limited to the method of dialogue and rational persuasion, storytelling, repetition, the use of analogies, encouraging learners to deduce answers themselves, and the method of discussion and questioning. It also addressed the process of teaching through illustrative drawings, linking it to the Prophet’s (peace be upon him) Hadith in Sahih Bukhari, under the chapter on Reqaq (softening of the heart) titled “On Hope and Its Length,” and connected it to technological advancements that integrate technology into the learning process—a requirement of the modern era.The researcher employed the inductive method by tracing the Hadiths related to this topic and the analytical method to analyze the Prophetic narrations, focusing on the educational methods they entail and their impact on academic outcomes. The study aimed to highlight the pedagogical approaches used by the Prophet (peace be upon him) in explanation and clarification, particularly his use of illustrative drawings. It analyzed how the Prophet (peace be upon him) employed this method through the Hadith on "Hope and Its Length."The research yielded several findings, the most notable being the diversity of the Prophetic teaching methods, which considered varying levels of intellect and understanding. Illustrative drawings were identified as highly effective in facilitating comprehension and conveying ideas. Additionally, the teacher’s role in selecting the most appropriate method to achieve desired outcomes was emphasized. The study concluded that Prophetic teaching methods are foundational for modern learning approaches.The research also included a collection of Prophetic Hadiths explained using illustrative drawings to ensure comprehension and make concepts clearer to the learner.
Keywords: Teaching Methods; Illustrative Drawing; Hope, and Lifespan